Háborús szövetség és vetélkedés: ahogy a lengyelkérdést az Osztrák-Magyar Monarchia néhány jelentős politikusa látta (1914–1918) = War-alliance and rivalry: the polish issue regarding by some significant politicians of the Austro-Hungarian Monarchy (1914–1918) - Tefner, Zoltán (Közép-Európai Közlemények, 2018)
The First World War signified the beginning of a new era also for the Polish society which also belonged to the Monarchy. The study has made effort to give a brief survey about the opinions about the future of Poland of many leading polititical outstanding figures in the Austro-Hungarian Monarchy. The study gives answers of two kind on this remarkable unusual question. On one hand, it gives a detailed description of the main concepts made by the Common Ministry of the Foreign Affaires during the four years of the war, on the other hand is treated in the paper the policy of Germany for and against the rebirth of a new Polish state. The author would like to make the problem of the competition between the two allied powers perfectly clear, why the rivarly in the Polish question led to unsucces. The question was temporarily solved by the antant with the restoration of Polish independence after the War. In the solution of the matter have been played a very important role also the Hungarian politcians as István Tisza and Gyula Andrássy junior. The discus of the two of them is rendered in the study lively and expressiv.